The Bessel wavelet transform of distributions in β μ ′ -space - Maurya J.S.; Upadhyay S.K. (My University, 2025)
In this paper, the inversion formula of the continuous Bessel wavelet transform of distributions in βμ′-space and its associated results with Bessel wavelet kernel containing non-vanishing moments of even orders weighted by xμ+ 1 2 are investigated by exploiting the theory of Hankel transform. © 2022 World Scientific Publishing Company.